Intercropping Pinto Peanut in Litchi Orchard Effectively Improved Soil Available Potassium Content, Optimized Soil Bacterial Community Structure, and Advanced Bacterial Community Diversity - Zhao, Ya; Yan, Caibin; Hu, Fuchu; Luo, Zhiwen; Zhang, Shiqing; Xiao, Min; Chen, Zhe; Fan, Hongyan (Frontiers in Microbiology, 2022)
Intercropping is widely used in agricultural production due to its capability of raising land productivity and providing an opportunity to achieve sustainable intensification of agriculture. In the present study, soil samples from 10~20 cm depth of intercropping Pinto peanut in litchi orchard and litchi monoculturing mode were established to determine soil attributes, enzyme activities, as well as the effect on soil bacterial diversity. On this basis, 16S rRNA V4-V5 region of soil bacterial communities in litchi /Pinto peanut intercropping mode (LP) and litchi monoculturing mode (CK) were detected by Illumina MiSeq sequencing platform. The results showed that the content of available potassium (AK) in LP was significantly higher than that in CK by138.9%, and the content of available nitrogen (AN) in LP was significantly lower than that in CK by 19.6%. The soil enzyme activities were higher in LP as a whole, especially the sucrase and acid protease were significantly higher by 154.4% and 76.5%, respectively. The absolute abundance and alpha diversity of soil microbiota were significantly higher in intercropping group. Most importantly, endemic species with significant difference in LP was higher by approximately 60 times compared to CK treatment. In the aspect of soil bacterial community structure, the dominant phyla of the two groups were Acidobacteria, Proteobacteria, Chloroflexi and Actinobacteria. At genus level, the absolute abundance of Flavobacterium, Nitrososphaera was significantly higher by 79.20%, 72.93%, while Candidatus_Koribacter significantly lower with amplitude of 62.24% in LP than in CK. Furthermore, the redundancy analysis (RDA) suggested that AK, which was highly associated with the dominant genera and phyla, is the vitally dominating environmental factors in LP groups, while in CK groups, it's AN and pH. Additionally, PICRUSt2 analysis indicated that intercropping improved the metabolic activity of bacteria which was highly correlated to the resistance of litchi root systems to soil soil-borne disease. Overall, this study expected to provide theoretical basis and technical support for the healthy intercropping cultivation of litchi.